PROBLEMATIKA LITERASI DALAM KONTEKS PENDIDIKAN (ISLAM) ABAD 21 - Zen Amrullah (Ta`Limuna: Jurnal Pendidikan Islam, 2023)
Abstract:This study aims to unravel the problems of 21st Century education, especially the problems of digital literacy. In principle, 21st century education provides a mandate, one of which is the development of critical thinking skills through digital literacy to students. This research is a library research. The results of this study are that the literacy culture of students is still in a very low position, which is still limited to the ability to access digital information only, even though students live amidst the spread of reading material in the internet world, including in the context of Islamic Religious Education. The novelty in this study, namely critical thinking skills, can be achieved if the literacy skills of students are not only limited to digital literacy but also informational literacy, ethical literacy and functional literacy, especially in the context of Islamic education in Indonesia